2021
DOI: 10.48022/mbl.2008.08012
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping and Molecular Characterization of Carbapenem-resistant Acinetobacter baumannii Strains Isolated from Intensive Care Unit Patients

Abstract: The emergence of multidrug-resistant Acinetobacter baumannii has partly increased treatment failure and patient mortality. Class D β-lactamases is an important mechanism of resistance to beta-lactam antibiotics in this species. This study aimed to investigate the relationship between the presence oxacillinase gene and genetic fingerprints of A. baumannii isolates from the intensive care unit of an Egyptian tertiary care hospital. One hundred and twenty A. baumannii clinical isolates were collected. Multiplex P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
1
1
1
Order By: Relevance
“…There are many reports indicating the presence of bla OXA-58 in A. baumannii clinical isolates throughout different parts of the world, where different rates of bla OXA-58 were previously detected in Tunisia, Egypt, and Algeria, recording 4 %, 9.1 %, and 14.7 %, respectively (Abouelfetouh et al, 2019). However, bla OXA-58 was absent in all A. baumannii isolates collected in this study, in agreement with the previous studies conducted in Mansoura, Egypt, by Benmahmod et al, (2019); Abozahra et al, (2021). However, other Egyptian studies of Al-Hassan et al, (2019);Hassan et al, (2021);Wasfi et al, (2021) reported different percentages of existence of this gene, recording 3.3 %, 1.9 %, and 2.9 %, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There are many reports indicating the presence of bla OXA-58 in A. baumannii clinical isolates throughout different parts of the world, where different rates of bla OXA-58 were previously detected in Tunisia, Egypt, and Algeria, recording 4 %, 9.1 %, and 14.7 %, respectively (Abouelfetouh et al, 2019). However, bla OXA-58 was absent in all A. baumannii isolates collected in this study, in agreement with the previous studies conducted in Mansoura, Egypt, by Benmahmod et al, (2019); Abozahra et al, (2021). However, other Egyptian studies of Al-Hassan et al, (2019);Hassan et al, (2021);Wasfi et al, (2021) reported different percentages of existence of this gene, recording 3.3 %, 1.9 %, and 2.9 %, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…The present study showed a moderate level of carbapenem resistance (65 %), in comparison with several Egyptian studies, including Al-Hassan et al, (2019);Benmahmod et al, (2019); Abozahra et al, (2021); Eshra, (2021); Ibrahim et al, (2022), which reported resistance rates of 95.7 %, 93 %, 98 %, 91.6 %, 88.9 %, and 100 %, respectively.…”
Section: Discussioncontrasting
confidence: 49%
“…MDR, WDR, and PDR observed in A. baumannii strains also express carbapenem resistance and occur through mechanisms including decreased permeability with changes in porin-like proteins, decreased intracellular antibiotic concentrations as a result of the activity of efflux pumps, and the production of enzymes such as β-lactamases [ 5 ].…”
Section: Highlight Key Pointsmentioning
confidence: 99%